INTEGRAL MONITORING OF HIGH-RISE BUILDINGS WHILE MINIMIZING THE NUMBER OF SENSORS - Valeriya Mixajlovna, Tolmacheva; Alexey Nikolaevich, Plotnikov; Mikhail Yurievich, Ivanov; Vasilij Yurievich, Amelin (Journal of Applied Engineering Science, 2020)
Considered current issues of automatic monitoring of high-rise buildings. A review of currently implemented monitoring methods is given. An analytical study of the effect of the ratio of the rigidity of the vertical and horizontal structural elements of buildings of various structural systems on the deformation of the vertical axis of the building was performed. The basis of the research is the solution of the differential equation of the elastic vertical axis of the building. By finding the extrema of the deformation function of the vertical axis, critical points of control of its angles of rotation are determined. As a result of the study, it was concluded that it is advisable to minimize the number of control points, with limited control at certain critical points. The position of the control points dividing the vertical axis of the building through ¼ of its length at the corners of the perimeter of the floors has been determined. It is shown that minimization is necessary due to difficulties in processing and analyzing big data (Big Data). As a result of the traditional manual calculation with the accepted design methods, it was found that the box-barrel structural system has the greatest deformations, the frame-link frame with the stiffness core has the smallest deformations, and outriggers do not always allow to radically increase the building stiffness. Studies were conducted on computer models of the same types of buildings, which confirmed this dependence. However, here the maximum rigidity was shown by the cross-wall model. This testifies to the features of modeling buildings in various ways and confirms once again the need to monitor not only high-rise buildings, but all non-standard ones. It is concluded that it is necessary to accumulate data on the deformations of buildings using automatic monitoring methods. It is shown that information on the technical condition of the building is complemented by information on the longitudinal deformations of vertical structures - columns, stiffness cores, measured by tensiometers on concrete, as well as dynamic stiffness, determined by the natural oscillation frequency of accelerometers. The principle of sensor grouping and the need to use integrated, integrated monitoring are shown.
Keywords: sensor; monitoring; deformation; forces; rigidity; deflection; frequency; inclinometer; strain gage; accelerometer